Visionary Infrastructure: Community Solar Streetlights in Highland Park. (August 2017) - Brennan, Shane
This article develops the concept of 'visionary infrastructure', defined as infrastructure that provides visions of and begins to build more sustainable futures for local communities, through the case study of a solar-powered street lighting project in Highland Park, Michigan, near Detroit. After the local utility company repossessed most of the city's streetlights, residents began building their own grassroots public lighting network. This infrastructure is visionary because it allows members of the largely African American community to determine precisely how their city is illuminated, and thus how seeing operates therein. By shifting control over the conditions of urban visuality from state and corporate officials to local residents, the lighting project intervenes in a long history of light on the street as a racialized tool of state surveillance and policing. And it shows how utility infrastructure can become a key site and mode of contemporary political resistance.